Unravelling the impact of the visible thinking approach on students’ learning experiences in a tertiary drama classroom - Mohd Nor, Zaamah; Christ Dass, Laura; Selvarani, Jebakumari (Universiti Teknologi MARA, 2025)
This qualitative study explored the impact of the Visible Thinking (VT) approach on students’ learning experiences. It was underpinned by Vygotsky's social constructivist theory (1962, 1978) and Ritchhart's Visible Thinking (VT) approach (2006), founded by Harvard University's Project Zero (PZ). The data was collected from a focus group discussion (FGD), followed by a thematic analysis of the transcribed data. The participants were students of Communication Through Drama (EPC522), a compulsory course for the third-semester students of the LG240 programme (Bachelor of Applied Language Studies-English for Professional Communication) at the Academy of Language Studies, Universiti Teknologi MARA, Shah Alam, Selangor, Malaysia. The study aimed to address the lack of emphasis on developing creative and critical thinking skills in Malaysian higher education, which has led to graduates struggling with problem-solving and employability. Despite the significance of interactive and structured thinking routines, their application in higher education remains underexplored, particularly in student-centred and collaborative learning environments. This research sought to fill this gap by investigating the effectiveness of the VT routines in enhancing interactive discussions and fostering higher-order thinking in a Malaysian university drama classroom. The findings revealed the positive impact and the feasibility of implementing the VT routine. Despite the challenges of conducting drama activities online, students embraced this new educational experience, creating a more interactive and studentcentred environment. These results also demonstrated how drama activities integrated with the VT routine can enhance students' interactive roles, thinking and communication skills, aligning with the Malaysian Higher Education Blueprint (2013–2025), which emphasises students’ mastery of communication and thinking skills to meet future demands